Terror y sexualidad. Lo ominoso en el cine de Lucrecia Martel - Rubino, Atilio Raúl (2015)
Based on the concept of the uncanny (Das Unheimliche), which was coined by Freud in 1919, this article has the purpose of analyzing elements that are characteristic of the horror genre in three films by the Argentine filmmaker Lucrecia Martel: La Ciénaga (2001), La niña santa (a.k.a. "The Holy Girl", 2004) y La mujer sin cabeza (a.k.a. "The Headless Woman", 2008). In these films, there are a number of supernatural and horror elements, such as the apparitions of the Virgin Mary and the African rat in La ciénaga, the signs and the divine callings in The Holy Girl, and the ghosts in The Headless Woman, among others. These elements, however, work as a fantasy and horror counterpoint for the real-world uncanny presences, which arise from the everyday things and threaten to disturb the order: death, murder and, in particular, non-normative sexualities, that is, active and free female sexuality, child and teenage sexuality, incest, homosexuality and lesbianism.
Documento incorporado en 2019 en el marco del "Programa de becas de experiencia laboral" de la Biblioteca Profesor Guillermo Obiols para estudiantes de Bibliotecología, a partir de un procedimiento técnico de captura de datos desarrollado por el personal del IdIHCS.
Keywords: Lucrecia Martel; Das Unheimliche; The uncanny; Horror movie; Argentine cinema; Sexuality; Monster children; Cinematografía; Terror; Martel, Lucrecia; Sexualidad disidente; Sexualidad femenina; Sexualidad adolescente; Sexualidad infantil